Cognitive rehabilitation among long COVID patients using vibratory and auditory treatment (VAT) is linked to BDNF - Mosabbir, Abdullah; Meltzer, Jed A.; Uryash, Arkady; Beroncal, Erika L.; Andreazza, Ana C.; Bartel, Lee (Frontiers in Cognition, 2025)
Cognitive dysfunction occurs in around 40% of long COVID (LC) patients, and in many cases appears second only to fatigue in prevalence. Vibratory and auditory treatment (VAT) within the gamma range has demonstrated improvements in symptoms associated with cognition and fatigue. In this open-label pilot study, we tested the effects of VAT on measures of cognition and fatigue in LC. Twenty patients were randomly divided into a treatment and a control group. Symptoms were monitored remotely through mobile apps and in-person visits before and after the treatment period. The treatment group received a device generating 40 Hz of VAT to take home and use every day from Monday to Friday for 4 weeks (i.e., 20 sessions over 28 days), whereas the control group did not use any device but followed the same data collection procedures. This study found that after 4 weeks of VAT, participants with LC exhibited increased performance in selective attention and response inhibition, an increased amount of circulating brain-derived neurotrophic factor (BDNF), and a reduced resting heart rate. We propose that VAT may be a useful rehabilitative tool for LC as well as other targeted populations that seek improvements in cognition or general health but are compromised immunologically or physically.